Capacity mechanisms for the long-term security of supply in electricity markets: an experimental study (2013)
Abstract: At the first years of deregulation, the academic discussion was first oriented to discuss the short-term efficiency and competitiveness of the electricity markets. Now, after more than twenty years of deregulation, the issue of the long-term security of supply has become increasingly relevant. A number of authors have used simulations and laboratory experiments to study capacity mechanisms in order to address this issue. This thesis explores the rationality of individuals’ decisions in a set of pilot experimental markets to test capacity mechanisms in electricity markets. We start from a previous experiment as base case, which is presented by Arango and Moxnes (2012).Thereafter; we take the second treatment with the capacity mechanism Procurement for long strategic reserve planning, by introducing a regulatory firm to the base case market. The third treatment test the capacity mechanism Centralized auctioning for capacity contracts, by introducing an auction for licenses system. We compare three treatments with six pilot experimental markets, two per treatment. We evaluate the performance in terms of the market’s long-term security of supply and the society’s welfare. Results from the pilot experiments provides only initial indications about the experiment. In Treatments 1 and 2, the experimental results show evidence of cyclical behavior in both prices and capacities. On the other hand, in Treatment 3, the experimental results show a more stable behavior due to the introduced auction for licenses system. Although the simulation tests indicate that both Treatments 2 and 3 should exhibit more stable behaviors in prices and capacities than Treatment 1, Treatment 2’s experimental results do not represent an improvement with respect to Treatment 1’s ones. In fact, results suggest that the regulatory firm introduced by Treatment 2 -Procurement for long strategic reserve planning- represents the less desirable scenario for market actors. On the contrary, Treatment 3’s experimental results are consistent with the simulation tests. In addition, the auction for licenses system introduced by Treatment 3 Centralised auctioning for capacity contracts- leads to more stable behaviors than both Treatments 1 and 2 results. These results suggest, first, that the Centralised auctioning for capacity contracts could help to stabilize the market without significant costs for the society’s welfare, and second, that the Procurement for long strategic reserve planning may not lead to any price stabilization or society’s welfare improvement